2005
DOI: 10.1110/ps.04738505
|View full text |Cite
|
Sign up to set email alerts
|

Modifications of human βA1/βA3‐crystallins include S‐methylation, glutathiolation, and truncation

Abstract: Disulfide bonding of lens crystallins contributes to the aggregation and insolubilization of these proteins that leads to cataract. A high concentration of reduced glutathione is believed to be key in preventing oxidation of crystallin sulfhydryls to form disulfide bonds. This protective role is decreased in aged lenses because of lower glutathione levels, especially in the nucleus. We recently found that human ␥-crystallins undergo S-methylation at exposed cysteine residues, a reaction that may prevent disulf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
12
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 52 publications
3
12
0
Order By: Relevance
“…The only crystallins where methylation was not detected were βB3 and the chaperone protein, αB crystallin, which lacks Cys residues. This study extends earlier reports of Cys methylation in γS, γD and βA3-crystallins from human lenses (Lapko et al, 2002, 2003, 2005; Searle et al, 2005). In the case of β-crystallins, these authors detected substantial levels of S-methylcysteine only in βA1/A3-crystallin.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The only crystallins where methylation was not detected were βB3 and the chaperone protein, αB crystallin, which lacks Cys residues. This study extends earlier reports of Cys methylation in γS, γD and βA3-crystallins from human lenses (Lapko et al, 2002, 2003, 2005; Searle et al, 2005). In the case of β-crystallins, these authors detected substantial levels of S-methylcysteine only in βA1/A3-crystallin.…”
Section: Discussionsupporting
confidence: 91%
“…S-methylation, an unusual post-translational modification (PTM), was first reported in human lens nearly a decade ago, (Lapko et al, 2002, 2003, 2005; Searle et al, 2005) but no plausible mechanism was proposed. More recent work (Wilmarth et al, 2006) on modifications of aged human lens crystallins indicated that methylation was found at other sites and was an abundant lens PTM; again no mechanism was suggested.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6][7] Methylation can also occur on the oxygen atoms of glutamate and aspartate (Omethylation) 8 and the sulfur atom of cysteine (S-methylation). 9 These modifications are carried out by a protein family called methyltransferases, which use S-adenosylmethionine as a sub-strate to transfer a methyl group. 10 Most studies of protein methylation have focused on methylated arginine and lysine residues.…”
Section: Introductionmentioning
confidence: 99%
“…The lens contains few major polypeptides, there is no protein turnover (9), and consequently post-translational modifications (PTMs) 2 accumulate in these life-long polypeptides over time. Abundant PTMs are racemization (10,11), methylation (12,13), and deamidation (14,15). Some lens proteins, such as the ␣-crystallins (16 -20) and aquaporin 0 (21)(22), also undergo progressive and extensive truncation.…”
mentioning
confidence: 99%